Modeling of the Nitric Oxide Transport in the Human Lungs - Karamaoun, Cyril; Van Muylem, Alain; Haut, Benoît (Frontiers in Physiology, 2016)
In the human lungs, nitric oxide (NO) acts as a bronchodilatator, by relaxing the bronchial smooth muscles and is closely linked to the inflammatory status of the lungs, owing to its antimicrobial activity. Furthermore, the molar fraction of NO in the exhaled air has been shown to be higher for asthmatic patients than for healthy patients. Multiple models have been developed in order to characterize the NO dynamics in the lungs, owing to their complex structure. Indeed, direct measurements in the lungs are difficult and, therefore, these models are valuable tools to interpret experimental data. In this work, a new model of the NO transport in the human lungs is proposed. It belongs to the family of the morphological models and is based on the morphometric model of Weibel. When compared to models published previously, its main new features are the layered representation of the wall of the airways and the possibility to simulate the influence of bronchoconstriction (BC) and of the presence of mucus on the NO transport in lungs. The model is based on a geometrical description of the lungs, at rest and during a respiratory cycle, coupled with transport equations, written in the layers composing an airway wall and in the lumen of the airways. First, it is checked that the model is able to reproduce experimental information available in the literature. Second, the model is used to discuss some features of the NO transport in healthy and unhealthy lungs. The simulation results are analyzed, especially when BC has occurred in the lungs. For instance, it is shown that BC can have a significant influence on the NO transport in the tissues composing an airway wall. It is also shown that the relation between BC and the molar fraction of NO in the exhaled air is complex. Indeed, BC might lead to an increase or to a decrease of this molar fraction, depending on the extent of the BC and on the possible presence of mucus. This should be confirmed experimentally and might provide an interesting way to characterize the extent of BC in unhealthy patients.